An experimental and numerical assessment of DCB tests on glass/polyester curved beams cut out from pipes - Rui Miranda Guedes (2008)
The aim of this work is to define a suitable procedure in order to measure the interlaminar fracture toughness of circumferential specimens cut out from ready-to-use glass reinforced polymer (GRP) pipes made by centrifugal casting. Double Cantilever Beam (DCB) tests were performed to assess the critical strain energy release rate in mode I (G(Ic)), which was considered equal to initiation values. In fact, the intrinsic heterogeneous composition of these GRP pipes promoted the occurrence of uncontrollable fibre bridging, which disturbed crack propagation and avoided the attainment of a smooth R-curve. The specimen's geometry leads the mode I loading into a complex stress state at the tip of the crack opening. This mixed-mode situation was numerically quantified using the virtual crack closure technique. For that purpose, a 2D FEM analysis with interface finite elements was used. A progressive failure analysis including a cohesive mixed-mode damage model was also performed. This numerical model reproduced the DCB tests and allowed the estimation of mode II influence on the measured G(Ic) values. Two different data reduction schemes, modified compliance calibration (MCC) and compliance-based beam method (CBBM), were used to calculate the G(Ic) values. Both methods are based on the classical beam theory since it was proved by comparison with curved beam theory that this gives accurate results for the present case. These methods were assessed using a numerical model.